Islam-based Civil Society and the State: Muhammadiyah’s Engagement in Indonesian Local Elections - Ahmad Fuad Fanani (Muslim Politics Review, 2025)
Religious organisations in Indonesia often forge close relations with the state, political leaders, and party elites. They devote much effort to gaining support from the state in order to protect their institutional interests. In this research, I consider Muhammadiyah’s relations with the state in the context of the organisation’s involvement in local politics and elections. I explore the nexus between institutional interest and epistemic influence, and the priority given to good state relations. This qualitative research uses data obtained through extensive literature study, analysis of election data, and in-depth interviews. This article argues that Muhammadiyah, as the second largest Islamic organisation with a vast network of educational, health and welfare institutions, places great store on having favourable links with the Indonesian state. Although rich in assets and financially secure, Muhammadiyah nonetheless requires access to state resources and goodwill from political and bureaucratic elites.